EFFECT OF POLYAMINES AND NAA APPLICATION ON YIELD OF TION ON YIELD OF MANGO ( MANGO (Mangifera indica Mangifera indica L.) CV. KESAR - VENU, AKULA; RAMDEVPUTRA, M. V. (The Bioscan, 2018)
A study was conduct to investigate the effect of polyamines and NAA on yield attributes like, fruit set, fruit retention, fruit drop, number fruits per panicle, number of fruits per tree, number fruits per hectare and fruit weight, fruit length, fruit volume in 15 years old trees of mango cv. Kesar, under Junagadh Agricultural University, Junagadh, saurastra region of Gujarat during 2015-16 and 2016-17. Results indicated that spermine 3 ppm increased fruit set (0.24 %), fruit retention (21.05 %), number of fruits per panicle (2.49), number of fruits per plant (394.68), fruit yield (99.61 kg/ tree & 9961.33 kg/ ha), fruit weight (288.97 g), fruit length (12.16 cm), fruit volume (282.04 ml) and minimum fruit drop (66.00%) in treated trees over non-treated trees at full bloom stage. Our results suggested that effect of polyamines on mango cv. Kesar to increased yield parameters.